Complexity in world trade of pears - Valenciano, Jaime de Pablo; Giacinti Battistuzzi, Miguel Angel (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2022)
This article describes the changes that are being experienced in the global trade in pears. Its purpose is to know if the processes of integration among countries are affecting their competitiveness in the international trade. Regarding the methodology utilized for this report, the Competitiveness Foreign Trade Index (CFTI) analyzes the competitiveness of a country for a particular product with its tariff nomenclature, covering its main export destinations, monitoring the rate of participation in accordance to the trends markets reflect, and thereby, assessing the competence. The result is seen clearly: The global trade competitiveness in pears is regional rather than global, resulting in being competitive solely on nearby markets subject to commercial agreements. The main solution would be related to an improvement of adapting their markets to a global dimension to increase competitiveness for their trade mark.